Pembangunan Model Clustering Dalam Pengelompokan Pengadilan Agama Berdasarkan Kasus Perceraian Dengan Menggunakan Algoritma K-Means - Sulistiyana Sulistiyana; Dian Ade Kurnia; Martanto (KOPERTIP : Jurnal Ilmiah Manajemen Informatika dan Komputer, 2021)
Divorce in domestic life is usually faced by married couples. During the life of a household, no one expects disputes that can end in divorce. A number of regions in Indonesia based on the Annual Reports of the Religious Courts from 2016, 2017, 2018, 2019 and 2020, it is known that there is a problem, namely an increase in the divorce rate in terms of the number of cases received by the Religious Courts. The problem of divorce cases is even increasing every year. To find out the Grouping of Divorce Cases Using the K-Means Algorithm in Indonesian Cities/Regencies. To perform this grouping using the k-means algorithm. . The dataset used consists of 410 with attributes of the causes that lead to divorce cases. Then preprocessing is carried out on the dataset to eliminate missing data. Then, the clustering technique was carried out using the k-means algorithm to be grouped. To get the best group, DBI calculation is used. The results of the research are expected to obtain grouping performance with the k-means algorithm. The results obtained show several groups with a DBI value of 0.19 with a number of clusters 2.